AN INTEGRATION OF WAQF AND VENTURA CAPITAL: A PROPOSED MODEL FOR INDONESIA - Tanjung, Hendri (Journal of Islamic Monetary Economics and Finance, 2018)
This study aims to find the appropriate model for the modus operandi of a financial institution called Waqf-Ventura Capital Syariah (WVCS). WVCS is integration between social finance (waqf) and commercial finance (Ventura capital). This WVCS has been adopted in Indonesia but the right form of operation is still yet to be found. In addition, this study also looks for appropriate contracts able to be practiced within the WVCS itself. WVCS is conceptualized based on the content analysis of cash waqf operations, profit and loss sharing modes and venture capital strategies. It has been found that there are at least 3 alternative models of operation for this WVCS. Firstly, the waqf fund is pooled into the capital; secondly, the waqf fund is pooled into a third-party fund; and thirdly, the waqf fund is pooled into both the capital and third party-fund. These unique operandi of WVCS could be adopted, as long as there are mudharabah dan musharakah contracts for development of the Indonesian Economy.